Mechanics of masonry structures strengthened with composite materials : selected, peer reviewed papers from the 4th International Seminar on Mechanics of Masonry Structures Strengthened with Composite Materials (MuRiCo4 2014), September 9-11, 2014, Ravenna, Italy - Tommaso, A. Di; Gentilini, C.; Castellazzi, G. (Key engineering materials, 2014)
Collection of selected, peer reviewed papers from the 4th International Conference on Mechanics of Masonry Structures Strengthened with Composite Materials (MuRiCO 2014), September 9-11, 2014, Ravenna, Italy. The 80 papers are grouped as follows: Chapter 1: General, Chapter 2: Masonry, Chapter 3: Materials, Chapter 4: Masonry and Composites, Chapter 5: Technical Reports The 80 papers consider such topics as an elastic-brittle fracture model for the robust post-peak analysis of masonry structures, investigating the distribution of dampness and salt in an outdoor full-scale masonry wall with wireless monitoring and radar testing, the influence of sample thickness and capping on the characterization of bedding mortars from historic masonry by the double punch test, first results of a three-dimensional finite element model of debonding between fiber-reinforced polymer and underlying masonry, and whether it is possible to repair detached composites effectively after masonry strengthening has failed. -- Construction-- Engineering-- Materials science.